2006
DOI: 10.1111/j.1467-9604.2006.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving classroom dynamics to support students' learning and social inclusion: a collaborative approach

Abstract: In this article, Mary Doveston and Marian Keenaghan discuss their work with teachers and students in developing more effective and satisfying interpersonal relationships in the classroom. Their approach focuses on increasing the capacity of a classroom community to address and measure its progress in the social and emotional competencies which that community has identified as being important. The principles of Appreciative Inquiry and Solution Focused Thinking underpin their approach to working with students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Although PP research has concentrated predominantly on student samples, researchers have also called for the application of positively oriented science to be applied to school staff as well as students (Calabrese, Hester, Friesen, & Burkhalter, 2010;Doveston & Keenaghan, 2006). For example, Waters (2011) advocated that positive psychology needs to be 'woven into the DNA of the wider school culture' (p. 85) so that its effects reach beyond students to also include teachers, non-teaching staff, parents and school leaders.…”
Section: Adopting a Pp Approachmentioning
confidence: 99%
“…Although PP research has concentrated predominantly on student samples, researchers have also called for the application of positively oriented science to be applied to school staff as well as students (Calabrese, Hester, Friesen, & Burkhalter, 2010;Doveston & Keenaghan, 2006). For example, Waters (2011) advocated that positive psychology needs to be 'woven into the DNA of the wider school culture' (p. 85) so that its effects reach beyond students to also include teachers, non-teaching staff, parents and school leaders.…”
Section: Adopting a Pp Approachmentioning
confidence: 99%
“…As the first Growing Talent for Inclusion (GTI) project (Doveston & Keenaghan, 2006) appeared to make a real difference to the social dynamics within a Year 8 class (12 to 13‐year‐old students) in a middle school, the model has been used and developed in other schools where the social dynamics within a particular class have been identified as barriers to learning and the development of positive peer relationships. These include a Year 3 class (7 to 8‐year‐olds) and a Year 5 class (9 to 10‐year‐olds) in two different primary schools, a Year 7 class (11 to 12‐year‐olds) in a middle school and a Year 8 class (12 to 13‐year‐olds) in a secondary school.…”
Section: The Contextmentioning
confidence: 99%
“…Researchers now suggest that the school experience needs to include specific interventions and activities that provide students with opportunities to explore friendships outside their social comfort zones (Doveston & Keenaghan, 2006;Leming, 1997). Salmivalli, Ojanen, Haanpaa, and Peets (2005) found that extracurricular mixing was the strongest determinant of students' ability to make friends across social boundaries.…”
mentioning
confidence: 98%